2002
DOI: 10.1046/j.1365-294x.2003.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the invasive cyanobacterium Cylindrospermopsis raciborskii

Abstract: Cylindrospermopsis raciborskii is a planktonic freshwater cyanobacterium that has become increasingly prevalent in tropical and temperate water bodies world-wide. This species is of concern from a water-quality perspective because of its known ability to produce toxins that can affect the health of humans and other animals. This study investigates genetic variation between strains of C. raciborskii isolated from freshwater rivers and reservoirs in Australia, Brazil, Germany, Hungary, Portugal and the USA. Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 32 publications
5
98
1
3
Order By: Relevance
“…It is also known to be capable of producing paralytic shellfish poisoning (PSP) (Lagos et al 1999;Neilan et al 2003). In a review of the cyanotoxin cylindrospermopsin, Griffiths & Saker (2003) describe recent developments in the application of molecular techniques for characterising strains of cyanobacteria that produce this toxin.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known to be capable of producing paralytic shellfish poisoning (PSP) (Lagos et al 1999;Neilan et al 2003). In a review of the cyanotoxin cylindrospermopsin, Griffiths & Saker (2003) describe recent developments in the application of molecular techniques for characterising strains of cyanobacteria that produce this toxin.…”
Section: Introductionmentioning
confidence: 99%
“…The explanation for the differences in the toxic levels found with the two microbiotests for the same cyanobacterial species (samples 13 and 14) is hence probably due to a different mechanism of toxicity induction by the Hungarian strain versus the Australian strain, with the Rapidtoxkit being very sensitive to the toxin(s) produced by the former. Neilan et al (2003) already reported the existence of three different phylogeographical groups of C. raciborskii strains collected from different parts of the globe on the base of HIP1 polymerase chain reaction fingerprint profile. He found that there was no relationship between the toxicity and the HIP1 polymerase chain reaction fingerprint profile, although paralytic shellfish poison and cylindrospermopsin producing strains were examined and at the same time no known toxins were found in European strains either.…”
Section: Resultsmentioning
confidence: 99%
“…These morphologies occur in other lakes (Bouvy et al, 1999;Neilan et al, 2003;Padisak, 2003), and maintain their identity through generations in culture with no transitional forms ). The circular trichomes may be either complete and partially overlapping circles or semi-circles.…”
Section: Determination Of Morphotype Abundancesmentioning
confidence: 94%
“…However, for the genus, there is considerable confusion about what defines a species, and the amount of strain level variability differs depending on the genetic region compared. Previous studies have shown that C. raciborskii originating from different parts of the world share nucleotide similarities of ≥99.1% for 16S rRNA, ≥98% for rpoC1, ≥97.5% for nifH, ≥94.5% for cpcBA intergenic spacer (cpcBA-IGS), and ≥91% for 16S-23S internal transcribed spacer region (ITS1) (Dyble et al, 2002;Neilan et al, 2003;Gugger et al, 2005). Compared to global variability, genetic sequence analysis of Lake Catemaco samples during different years and seasons consistently show very high genetic similarity.…”
Section: Nitrogen Phenotypic Plasticity and Taxonomymentioning
confidence: 96%